INSTITUTIONAL TRANSFORMATION: INTRODUCTION TO THE SPECIAL ISSUE - Moore, Janet C. (Online Learning, 2006)
This special issue of the Journal of Asynchronous Learning Networks focuses on institutional transformation, including insights into business models. This introduction points to additional Sloan-C resources on cost effectiveness and institutional commitment.